PENGARUH BRAND IMAGE, HARGA, KUALITAS DAN KEMASAN TERHADAP MINAT BELI KONSUMEN JAMU SABDO PALON DI SUKOHARJO - Riza Kurniasari; Diana Leli Indratno; R. Suprono Wahyujatmiko (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to determine and analyze the effect of brand image, price, quality, and packaging on the buying interest of consumers of Sabdo Palon herbal medicine in Sukoharjo. The data collection method used in this study was distributing questionnaires. The population used in this study were respondents who had bought Sabdo Palon herbal medicine. The sample in this study was 100 respondents and the technique used was the Non Probability Sampling technique with a Purposive Sampling approach. This study uses multiple linearregression analysis as a method of data analysis. With the regression equation Y= 0,593 + 0,882 X1 – 0,246 X2 + 0,075 X3 + 0,178 X4. The results of this study indicate that brand image has a significant effect on purchase intention, the price has an effect but is not significant on purchase intention, quality has a significant effect on purchase intention while packaging has a significant effect on purchase intention. Keywords: Brand Image, Price, Quality, Packaging ,and Purchase Intention